Closed Loop Control of Soft Switched Interleaved Buck Converter - R. Shenbagalakshmi; Sree Renga Raja (Institute of Advanced Engineering and Science, 2012)
Design, Modeling and Simulation of a closed loop control is presented for Interleaved Buck Converter with Soft Switching. The features of the closed loop system are to reduce the switching losses and load current sharing among the parallel connected converters. The control system of the converter is designed using PWM technique. In order to improve the transient response and dynamic stability of the converters, the controller parameters are designed based on current mode control. Resonant components thus designed enable the application of zero current switching for both the converters connected in parallel thereby maintaining greater efficiency and minimizing voltage and current oscillations. The system analysis, design and performance are verified through simulation using MATLAB/Simulink environment. The simulation approach reveals the high speed dynamic performance of the closed loop system designed using robust PID controller. The laboratory prototype of the Buck converter is developed to verify the controller platform using PIC16F877A microcontroller.DOI: http://dx.doi.org/10.11591/ijpeds.v2i3.832